The Effect Of Marketing Strategy on Consumers Interest Buying at Nibra's House Cileungsi - Romandhini, Anisa; El Hasan, Sawqi Saad; Herawati, Ermi (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
This research was conducted to determine the effect of marketing strategies (product, price, place, promotion, people, process and physical evidence) on consumer interest in buying Nibra's House Cileungsi products. The method used is quantitative with sampling in this study as many as 100 respondents using accidental sampling technique. Data analysis techniques in this study used multiple linear regression analysis with partial regression test (t-test). The calculation process is assisted by SPSS 22 application program. The test results show that there is no significant effect between product marketing strategies on consumer buying interest at Nibra's House Cileungsi. There is no significant influence between the price marketing strategy on consumer buying interest at Nibra's House Cileungsi. There is a significant influence between the place's marketing strategy on consumer buying interest at Nibra's House Cileungsi. There is a significant influence between promotional marketing strategies on consumer buying interest at Nibra's House Cileungsi. there is no significant influence between human marketing strategies on consumer buying interest at Nibra's House Cileungsi. There is a significant influence between the process marketing strategy on consumer buying interest at Nibra's House Cileungsi. Then there is a significant influence between the physical evidence marketing strategy on consumer buying interest at Nibra's House Cileungsi. And for product, price, place, promotion, process and physical evidence variables simultaneously have a significant effect on purchase intention